Hemoglobin A1C testing frequency among patients with type 2 diabetes within a US payer system: a retrospective observational study. (2nd November 2021) - Weiss, Tracey; Edwards, Alison; Lautsch, Dominik; Rajpathak, Swapnil; Snow, Kenneth
Abstract: Objective: The American Diabetes Association (ADA) guidelines recommend A1C testing schedules for patients with type 2 diabetes; however, level of real-world guideline adherence remains unclear. The current study evaluated A1C testing frequency and its association with glycemic control and cardiovascular outcomes. Methods: A retrospective study was conducted utilizing Aetna's Enterprise Data Warehouse. Adult patients with a medical claim for type 2 diabetes in 2017 (index date) were included. Patients had continuous enrollment through December 2019 and ≥1 reported A1C measurement from 2017 to 2019. Follow-up was up to 36 months post-index date. Results: Of the 112, 572 eligible patients, 50.0% were female and median age was 70 years; 32.9% of patients with controlled baseline A1C (<8%, 64 mmol/mol) received less than the 2 tests/year recommended by the ADA, while 60.6% of patients with uncontrolled baseline A1C received less than the quarterly testing recommended by the ADA. More frequent testing was associated with age (65–75 years), uncontrolled baseline A1C and presence of comorbidities. In separate multivariable models, 2–3 A1C tests/year were associated with greater likelihood of A1C < 8% (64 mmol/mol) vs. <2 tests/year (OR = 1.07, 95% confidence interval [CI] 1.02–1.12), while >3 tests/year was associated with a modestly increased risk of cardiovascular events vs. <2 tests/year (OR = 1.08, 95% CI 1.01–1.15). Conclusions: A large proportion of type 2 diabetes patients were not tested per guideline recommendations. The relationship between A1C testing frequency and glycemic control was inconsistent, though there was a significant association between more frequent testing and experiencing a CV event.